2019
DOI: 10.3390/en12030502
|View full text |Cite
|
Sign up to set email alerts
|

Seepage Safety Assessment of Concrete Gravity Dam Based on Matter-Element Extension Model and FDA

Abstract: As an important infrastructure project, the concrete gravity dam plays an extremely important role in hydropower generation, irrigation, flood control, and other aspects. Seepage is an important factor affecting the stability of concrete gravity dams. Seepage safety assessment is of great significance to the safe operation of the dams. However, the existing seepage safety assessment models are not dynamic, and the correlation among indicators is often neglected and the overall seepage safety of the concrete gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…where N is the name of the thing, C is the feature of the thing, and v is the characteristic value of the feature C, usually expressed as a determined value or numerical interval. When a thing has multiple attributes, the traditional matter element can be expressed as in Equation (1) [56]:…”
Section: Meecm Theorymentioning
confidence: 99%
“…where N is the name of the thing, C is the feature of the thing, and v is the characteristic value of the feature C, usually expressed as a determined value or numerical interval. When a thing has multiple attributes, the traditional matter element can be expressed as in Equation (1) [56]:…”
Section: Meecm Theorymentioning
confidence: 99%
“…Its theoretical background is in matter-element theory and extension set theory. Through the qualitative analysis of a matter-element, combined with the quantitative calculation of a correlation function, it transforms various indexes that influence the object under evalua-tion into a compatible problem; thus, a comprehensive evaluation model [35][36][37][38][39][40][41] that is more in line with objective reality is obtained. The calculation process of the fuzzy matter-element analysis method is as follows:…”
Section: Analytical Hierarchy Process (Ahp)mentioning
confidence: 99%
“…Previous studies [5][6][7][8][9][10][11] have shown that base deformations caused by the displacement of the structure model under the influence of applied loads when bringing the model to failure can spread to a considerable depth. In this case, the physical and mechanical characteristics of rocks lying below those located directly under the structure can affect the nature of destruction and the magnitude of the breaking load.…”
Section: Introductionmentioning
confidence: 99%